Impact of Microfinance on women empowerment through Self-Help-Groups in Alwar District, India - et. al., Rejoice Solomon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Empowerments of women become a main motive of the nation. As they are the foundation for the growth, peace and Equality of the nation.70% of the worlds’ population are of poor women. And they were not considered by any formal or non formal institution for the credit worthiness but it is microfinance institutions that came forward to avail the facility of loan to them with the help of Self-Help-group. The motive of this paper is to know the dimensions by which empowerment of women would be take place through microfinance self-help-group. For the collection of data a survey method was used on the 550 women of Alwar District but for the study only 496 questionnaires was used as the 54 questionnaire was not completely. The collected data was analysed in SPSS, Factor Analysis, Pearson r and Dependent and independent variables were considered did to know the impact of microfinance on empowering women by SHGs of Alwar, Rajasthan. The study shows a positive relationship of in the economical and social empowerment of women with microfinance.